POTENSI PREBIOTIK BISKUIT SUBSTITUSI TEPUNG TERIGU DENGAN UMBI GEMBILI (Dioscorea esculanta) SEBAGAI PMT BALITA - Aulia Syahrin Tamzis (2022)
Intestinal inflammation due to enteric infections repeatedly called pediatric environmental enteropathy (PEE) founded in stunted children. Thus initiating to development a functional food product containing prebiotic as an effort to maintain the diversity of intestinal microflora and prevent enteric infections. The purpose of this study is to formulate biscuit that substitute wheat flour with gembili tubers as functional food containing inulin to prevent enteric infection in toddlers. In addition, the specific purpose of this study is to analyze the nutrition content, inulin content, and organoleptic properties of biscuit. This study is using a completely randomized design with two repetitions as research method. Nutrition and inulin content data analyze using One-way Anova and continue with Duncan's test, while organoleptic data analyze using Kruskal Wallis test and continue with Mann Whitney test. The result of the analysis show that the composition of substitution of wheat flour with gembili tubers is significant effect water, ash, protein, carbohydrate, and inulin content (p<0.05). However, it has no significant effect on fat content. For organoleptic properties, the difference composition of substitution wheat flour with gembili tubers is significant effect the texture and taste of biscuit (p<0.05). However, it did not significant effect the color and scent of biscuit. The selected formula in this study was biscuit 4 with composition 100% substitution wheat flour with gembili tubers.